Challenges and trends in apomorphine drug delivery systems for the treatment of Parkinson's disease - Nrupa Borkar; Huiling Mu; René Holm (Elsevier, 2018)
Parkinson's disease (PD) is a chronic debilitating disease affecting approximately 1% of the population over the age of 60. The severity of PD is correlated to the degree of dopaminergic neuronal loss. Apomorphine has a similar chemical structure as the neurotransmitter dopamine and has been used for the treatment of advanced PD patients. In PD patients, apomorphine is normally administered subcutaneously with frequent injections because of the compound's extensive hepatic first-pass metabolism. There is, hence, a large unmet need for alternative administrative routes for apomorphine to improve patient compliance. The present review focuses on the research and development of alternative delivery of apomorphine, aiming to highlight the potential of non-invasive apomorphine therapy in PD, such as sublingual delivery and transdermal delivery. Keywords: Apomorphine, Drug delivery, Parkinson's disease, Alternative apomorphine therapy, Non-invasive delivery, Excipients